2011
DOI: 10.1111/j.1468-3083.2011.04388.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe diffuse non‐scarring hair loss in systemic lupus erythematosus – clinical and histopathological analysis of four cases

Abstract: The severe type of hair loss in patient with SLE presents a unique set of clinical, dermoscopic and histopathological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 16 publications
1
28
0
2
Order By: Relevance
“…21,31 For non-scarring cases, previous studies on fewer than 30 subjects had reported telangiectasia, scaling, reduction in number and diameter of hair, along with hypopigmented hair shafts. 5,6 To the best of our knowledge, we have collected trichoscopic findings of normal-looking or nonscarring scalp from the largest group of SLE patients. As there is limited data on trichoscopy in normal Asian population, enrolling normal controls with similar age and gender distribution for comparison has allowed assessments for the odds of having SLE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,31 For non-scarring cases, previous studies on fewer than 30 subjects had reported telangiectasia, scaling, reduction in number and diameter of hair, along with hypopigmented hair shafts. 5,6 To the best of our knowledge, we have collected trichoscopic findings of normal-looking or nonscarring scalp from the largest group of SLE patients. As there is limited data on trichoscopy in normal Asian population, enrolling normal controls with similar age and gender distribution for comparison has allowed assessments for the odds of having SLE.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4 In addition, scalp changes, especially telangiectasias, were also frequently observed throughout the scalp of SLE patients. 1,5,6 Histopathological study and direct immunofluorescence (DIF) of these changes had demonstrated specific lupus erythematosus features, suggesting a direct effect of SLE activity on the scalp. [5][6][7] Trichoscopy is a non-invasive tool that has become standard practice in hair and scalp evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermoscopy shows scalp atrophy, loss of the honeycomb pattern in black patients, loss of follicular opening, arborizing telangiectasia, and keratotic plugs. The presence of red dots indicates that the disease is still reversible [67][68][69][70].…”
Section: Lupus Erythematosusmentioning
confidence: 99%
“…Die Dermatoskopie zeigt hier eine Atrophie der Kopfhaut, einen Verlust des Wabenmusters bei Patienten mit schwarzer Hautfarbe, einen Verlust von Follikelöffnungen, verzweigte Teleangiektasien und eine Hyperkeratose. Das Vorhandensein roter Punkte deutet darauf hin, dass die Erkrankung noch reversibel ist [67,68,69,70]. …”
Section: Lupus Erythematodesunclassified